U-Shaped relationship of insulin-like growth factor I and incidence of nonalcoholic fatty liver in patients with pituitary neuroendocrine tumors: a cohort study - Hu, Yan; Yuan, Chen; Abdulnaimu, Muila; Memetmin, Jimilanmu; Jie, Zhang; Tuhuti, Aihemaitijiang; Abudueini, Hanikzi; Guo, Yanying (Frontiers in Endocrinology, 2024)
Context: Although the role of insulin-like growth factor I (IGF-1) in nonalcoholic fatty liver disease (NAFLD) has garnered attention in recent years, few studies have examined both reduced and elevated levels of IGF-1.Objective: The aim of this study was to examine the potential relationship between IGF-1 levels and the risk of new-onset NAFLD in patients with pituitary neuroendocrine tumors (PitNET).Methods: We employed multivariable Cox regression models and two-piecewise regression models to assess the association between IGF-1 and new-onset NAFLD. Hazard ratios (HRs) and their corresponding 95% confidence intervals (CIs) were calculated to quantify this association. Furthermore, a dose-response correlation between lgIGF-1 and the development of NAFLD was plotted. Additionally, we also performed subgroup analysis and a series sensitivity analysis.Results: A total of 3,291 PitNET patients were enrolled in the present study, and the median duration of follow-up was 65 months. Patients with either reduced or elevated levels of IGF-1 at baseline were found to be at a higher risk of NAFLD compared to PitNET patients with normal IGF-1(log-rank test, P < 0.001). In the adjusted Cox regression analysis model (model IV), compared with participants with normal IGF-1, the HRs of those with elevated and reduced IGF-1 were 2.33 (95% CI 1.75, 3.11) and 2.2 (95% CI 1.78, 2.7). Furthermore, in non-adjusted or adjusted models, our study revealed a U-shaped relationship between lgIGF-1 and the risk of NAFLD. Moreover, the results from subgroup and sensitivity analyses were consistent with the main results.Conclusions: There was a U-shaped trend between IGF-1 and new-onset NAFLD in patients with PitNET. Further evaluation of our discoveries is warranted.